Evaluating the urban metabolism sustainability of municipal solid waste management system: An extended exergy accounting and indexing perspective. (15th October 2021) - Liu, J.; Goel, A.; Kua, H.W.; Wang, C.H.; Peng, Y.H.
Graphical abstract: Highlights: Extended Exergy Accounting and Urban Metabolism Sustainability Index were proposed. This methodology and metric were applied to a public garden in Singapore. Non-energetic externalitiesare specific modeled in homogeneous exergy terms. Uncertainty analysis was conducted to confirm the reliability of the calculated results. Sensitivity analysis was carried out and potential improvements were proposed. Abstract: In this study, Extended Exergy Accounting was adopted to develop an accounting model to evaluate the performance of a Municipal Solid Waste Management System. Furthermore, urban metabolism sustainability index for waste was also proposed to represent the unified society-economy-environment impacts of the MSWMS under the framework of a comprehensive sustainability evaluation. A detailed analysis of wood and horticultural waste treatment scenarios in Singapore was done as a case study. It was found that the gasification scenario theoretically performs significantly better than the incineration scenario, in terms of energy carrier consumption, emissions, thermodynamic efficiency and sustainability. Analysis results show that, if extrapolated to Singapore's total wood and horticultural waste, gasification technology has potential to reduce energy consumption and increase electricity output. An uncertainty analysis was carried out and it was found that the main extended exergetic parameters of the two scenarios considered were in the range of 3–8%, thus confirming the reliability of the accounting results. A sensitivity analysis of the urban metabolism sustainability index for waste was conducted for the gasification scenario to identify key influencing factors and seek potential improvements; this was done by considering changes in four variables: transportation distance, electrical efficiency, working hour increment and gross capital cost per ton waste treated. It was found that, to ensure the feasibility and sustainability of gasification scenario, the following are required: keeping the electricity production efficiency greater than 21.33%; the transportation distance between the gasification power plant and source of wood and horticultural waste should be kept within 17.08 km; employment of per kton annual treatment capacity should be less than 0.14 workers; wood and horticultural waste source should control the waste collection frequency of no more than 3 times per day and the number of workers participating in the collection each time is less than 4 persons, totaling to 12 workers per day.